An Approach to Eddy Current Reduction in Laser Powder Bed Fused High Silicon Steel Considering Manufacturing Influences - Urban, Nikolaus; Masuch, Michael; Paduch, Jan; Franke, Jorg (2021 11th International Electric Drives Production Conference (EDPC), 2021)
Additive manufacturing (AM) is a primary forming technology that makes it possible to produce previously impossible geometries and tailored properties by selectively adding material to a workpiece under computer control. For small to medium quantities, the processes grouped under this technology are already established in the industry. Metals are often processed by laser powder bed fusion (PBF- LB/M). With PBF- LB/M, different powder materials can be processed with identical system equipment. With the successive spread of this production technology, the processing of functional materials in the electro-mechanical-engineering industry is increasingly becoming the focus of interest for users. The processing of copper by PBF - LB/M is already state of the art. Soft magnetic materials are currently the subject of research work, and promising results have already been published. The realization of components that provide lowest possible energy losses is also of decisive importance in the context of electromagnetic energy converters. According to the state of the art, multi-material systems of metal and polymer or ceramic, as used for the conventional design of sheet metal packages or soft magnetic composites (SMC) cores, cannot be processed on PBF-LB/M systems. As an alternative, area-filling structures, which cannot be produced conventionally, are known to reduce losses. By including thin non-consolidated areas inside the workpiece, eddy current paths can be interrupted and losses reduced. Initial studies on this show promising potential. In this publication, different area-filling patterns are numerically evaluated based on the eddy current density in the sample crosssection. However, PBF -LB/M-specific manufacturing influences, such as welding through thin powder layers, prevent the direct transfer of the numerical investigations into practice. Therefore, a comparison is made in experimental studies, which qualitatively confirm the findings and provide promising approaches for loss reduction.